(untitled) (Research, Society and Development, 2024)
The investigation of pathological manifestations in buildings is fundamental to the development of effective intervention strategies aimed at correcting existing problems and preventing future damage. The main objective of this article is to present the results of a detailed analysis of the pathological manifestations identified in the São Pedro and São Paulo Apóstolos Church, located in Belo Jardim, Pernambuco (Brazil). The study’s methodology consisted of qualitative field research, of the case study type, carried out through technical visits, photographic records and the creation of damage maps. After a thorough visual inspection, the anomalies were analyzed and compared with specialized literature. The results showed that the most common pathological manifestations are caused by the presence of humidity and that cracks due to probable corrosion of the reinforcement were also identified. Based on the results obtained, the study proposed therapies and interventions to mitigate the problems identified, emphasizing the importance of these proposals to ensure the preservation of the church for future generations.